IMPROVING TEACHER COMPETENCE THROUGH ASSISTANCE IN WRITING CLASSROOM ACTION RESEARCH - Dian Anggraeni Maharbid; Markum Markum (Prima: Jurnal Pendidikan Matematika, 2023)
The purpose of this study is to determine the problems experienced by teachers in professional improvement and functional positions, the problems experienced by teachers are lack of ability in writing scientific papers caused by not understanding the stages of writing and conducting research. This type of research is qualitative research with a descriptive method that aims to describe the problems faced by teachers in writing classroom action research and improving teacher abilities through assistance. Based on the results of the study, it is known that the results of scientific papers written by teachers can be said to be worthy of publication in scientific journals